Free : my search for meaning - Knox, Amanda (Grand Central Publishing, 2025)
"Amanda Knox spent nearly four years in prison and eight years on trial for a murder she didn't commit-and became a notorious tabloid story in the process. Though she was exonerated, it's taken more than a decade for her to reclaim her identity and truly feel free. Free recounts how Knox survived prison, the mistakes she made and misadventures she had reintegrating into society, and culminates in the untold story of her return to Italy and the extraordinary relationship she's built with the man who sent her to prison. It is the gripping saga of what happens when you become the definition of notorious but have quietly returned to the matters of a normal life-seeking a life partner, finding a job, or even just going out in public. In harrowing (and sometimes hilarious) detail, Amanda tells the story of her personal growth and hard-fought wisdom, recasting her public reckoning as a private reflection on the search for meaning and purpose that will speak to everyone persevering through hardship"--